(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2014)
It has been previously shown that the virus of acute African swine fever (ASF) infection causes significant alterations in the population of white blood cells. Thus, it has been assumed that ASF disrupts hematopoietic homeostasis through an unknown mechanism. To test this assumption, we have conducted this study to evaluate the changes of red blood cells (RBCs) in peripheral blood during experimental ASF virus infection. Light microscopy of erythropoiesis in this case showed distinct features of dyserythropoiesis. From the beginning of infection, juvenile forms of RBCs, such as the largest cells of erythron, rubriblasts, were observed in the peripheral blood of infected pigs. Among the erythroid precursors, up to 60% of all cells were binucleated, which indicates that acute ASF infection is accompanied with the emergence of pathological forms of RBCs.